Gated communities in the southern area of the city of Santiago, 2010-2019 - Navarro, Juan José (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The specialized literature has characterized closed urbanization as one of the fundamental dimensions of the neoliberal city. Thus, it is part of the landscape of different Latin American cities. Closed construction continues to proliferate and diversify in its forms, being located in different territories where conditions for its reproduction exist. The objective of this study was to analyze gated communities in the municipalities of Puente Alto, La Florida, San Bernardo, Maipú, Peñaflor, Padre Hurtado and Talagante, located south of the city of Santiago de Chile. The methodology was based on information obtained from building permits, the real estate portal Toctoc and satellite images integrated with GIS software. Based on the above, the characteristics of this type of complexes were examined in order to demonstrate their spatial behavior. The general results establish a proliferation both in the communes that are part of the consolidated urban boundary and in those that are outside, as well as a range of typologies oriented to different social strata, from social projects to luxury ones. Despite being part of the current territorial configuration of the study area, the gated communities present differences among themselves and with respect to the rest of the surrounding constructions, which perpetuate processes of spatial fragmentation.